The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2016
DOI: 10.1136/bcr-2016-216246
|View full text |Cite
|
Sign up to set email alerts
|

A unique presentation of a complex haemorrhagic adrenal pseudocyst

Abstract: A man aged 33 years presented with a 3-day history of left-sided testicular discomfort. Clinical examination revealed a large left-sided varicocele. He was referred for a testicular ultrasound, which demonstrated a moderate left-sided varicocele and an associated large suprarenal mass. An urgent (CT) scan was arranged which confirmed this, with associated compression of adjacent structures, including the left kidney and left renal vessels. The patient was admitted 1 week following the CT scan with features of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…There was a case report of a haemorrhagic suprarenal pseudocyst presenting as a varicocele. 8 Another case report documented an adrenal pseudocyst in pregnancy which had to be excised at laparotomy while the pregnancy was carried to term delivery. 9 10 Treatment is done by surgical excision, which can be done laparoscopically depending on the size of the lesion.…”
Section: Discussionmentioning
confidence: 99%
“…There was a case report of a haemorrhagic suprarenal pseudocyst presenting as a varicocele. 8 Another case report documented an adrenal pseudocyst in pregnancy which had to be excised at laparotomy while the pregnancy was carried to term delivery. 9 10 Treatment is done by surgical excision, which can be done laparoscopically depending on the size of the lesion.…”
Section: Discussionmentioning
confidence: 99%
“…In a systematic review, 80% of bleeding adrenal tumours were benign (26). Common benign tumours underlying bleeding include phaeochromocytoma (15), cortical lesions, adrenal pseudo cysts and lipomas (21,30). Malignant adrenal tumours associated with adrenal haemorrhage include adrenocortical carcinoma and metastasis (26).…”
Section: Discussionmentioning
confidence: 99%
“…In the published case reports, most patients are initially treated conservatively (5,(10)(11)(12)(13)(14). Surgical resection has been performed electively by either the open or laparoscopic approach (9,21). CT scan may be performed during follow-up to monitor the size of the haematoma and evaluate any underlying lesion (22).…”
Section: Original Articlementioning
confidence: 99%
“…However, they can cause symptoms through repeated episodes of trauma, infection or bleeding 2 . When they do, they are often non-specific symptoms, for example respiratory symptoms as highlighted in our case study 4 , left testicular discomfort as identified by a case report in the United Kingdom 8 and epigastric pain and abdominal distension 15 . An Indian case report even reported unusual presentations of hypertensive retinopathy, virilization and bleeding diathesis 17 .…”
Section: Introductionmentioning
confidence: 78%